Regulation of pyrimidine biosynthesis in the biocontrol bacterium Pseudomonas aureofaciens - Gore, Lou V; West, Thomas P (Folia microbiologica, 2025)
The regulation of the pyrimidine biosynthetic pathway by pyrimidines was investigated in the biological control agent Pseudomonas aureofaciens ATCC 17418. Using succinate as a carbon source, orotic acid or uracil supplementation had a repressive effect in ATCC 17418 cells on dihydroorotate dehydrogenase or orotidine 5'- monophosphate decarboxylase activity but only orotic acid supplementation appeared to repress the level of orotate phosphoribosyltransferase activity. In glucose-grown ATCC 17418 cells, orotic acid supplementation appeared to repress the level of phosphoribosyltransferase or decarboxylase while uracil supplementation depressed the dihydroorotase, dehydrogenase, and decarboxylase activities. The pyrimidine auxotrophic mutant strain GW-2, isolated from ATCC 17418 using chemical mutagenesis and resistance to 5-fluoroorotic acid, was found to be deficient for orotidine 5'-monophosphate decarboxylase activity. Pyrimidine limitation of the succinate-grown mutant strain cells resulted in only a slight derepression of transcarbamoylase activity while pyrimidine limitation of glucose-grown mutant cells caused a derepression of the four active pyrimidine biosynthetic enzyme activities relative to their activities in the mutant cells grown with excess uracil. The control of the known regulatory enzyme aspartate transcarbamoylase was examined in P. aureofaciens ATCC 17418. Transcarbamoylase activity was shown to be inhibited by pyrophosphate, ATP, UTP, and ADP. It was concluded that the pyrimidine biosynthetic pathway in P. aureofaciens ATCC 17418 was subject to regulation at the transcriptional level and at the level of aspartate transcarbamoylase activity, which could be valuable in comprehending its nucleic acid metabolism as well as its taxonomic assignment to the Pseudomonas chlororaphis homology group.
Keywords: bakteriální proteiny; Oxidoreductases Acting on CH-CH Group Donors; Orotidine-5'-Phosphate Decarboxylase; oxidoreduktasy působící na CH-CH vazby; Glucose; Regulation; Biosynthesis; Dihydroorotate Dehydrogenase; kyselina orotová; Uracil; Pyrimidines; regulace genové exprese u bakterií; kyselina jantarová; aspartátkarbamoyltransferasa; glukosa; Orotic Acid; Pseudomonas; Biosynthetic Pathways; pyrimidiny; orotátfosforibosyltransferasa; uracil; Aspartate transcarbamoylase; Orotate Phosphoribosyltransferase; Bacterial Proteins; biosyntetické dráhy; Succinic Acid; Aspartate Carbamoyltransferase; dihydroorotátdehydrogenasa; Gene Expression Regulation, Bacterial; orotidin-5'-fosfátdekarboxylasa